El Procedimiento Sancionador Administrativo Disciplinario en la Ley Nº 30057 Servicio Civil: nuevos lineamientos - Zavaleta Diaz, Gustavo Alberto Martín (2019)
It is necessary, as a consequence, of the new political - legal reality, existing in Latin America and the Caribbean, that the Ius Puniendi of the State, not only expresses itself, in the Executive and Judicial Power, but also, in the Legislative Power, having each of these punitive expressions, different nature: politics in the Legislative Power; criminal in the judiciary and administrative sanctioning in the executive branch. The evolutionary process of the Public Function is analyzed, determining its essential characteristics, to subsequently make a dogmatic, normative analysis of the agents or subjects that integrate the public function, in its three main blocks: Senior State Officials (Art. 99 of the Constitution of 93) Public Officials and Employees (Law No. 30057 of the Civil Service and its Regulations). Similarly, new innovations, both substantive and adjective, are developed in an orderly manner, which brings the Civil Service Law, in relation to the development, of the disciplinary administrative disciplinary procedure, which has essential characteristics and which differentiates it from the sanctioning procedure: corrective, ethical and functional administrative responsibility.